إدارة تسويق الخدمات الطبّية بالتطبيق على مشفى الأسد الجامعي باللاذقية ومشفى الباسل بطرطوس - ديوب, محمد عباس; عطية, هنادي رمضان (Latakia University Journal - Economic and Legal Sciences Series, 2019)
باعتبار أن نظام الخدمات الطبية المعمول به في أي مجتمع من المجتمعات يكون دقيق الارتباط بالحالة الاجتماعية والاقتصادية لأفراد هذا المجتمع، حتى إنه من الممكن القول: إن مستوى الخدمات الطبية لمجتمع من المجتمعات يعتبر مقياساً لتقدمه الاجتماعي والاقتصادي. فإنه وفي هذا الإطار يتناول البحث الخدمات الطبية المقدمة من قبل المشافي بأنواعها، كما يركز على موضوع تسويق الخدمات الطبية في المشافي وضرورة وجود إدارة خاصة بالتسويق في كل مشفى لتقوم بالدراسات التسويقية اللازمة والضرورية للتعرف على حاجات المرضى واتجاهاتهم المدركة، ومن ثم إمكانية تقدير الطلب على الخدمات الطبية والسياسات التسويقية التي تكفل تقديم المشفى لأفضل الخدمات واستحواذ كل ما هو جديد من أجهزة وأدوات طبية وتقديم الخدمات التي تساهم في إشباع حاجات المريض وتحقيق رضاه. Since the Medical Services System employed in any community is closely related to the social and economic status of the members of the community, we can say that the level of medical services of any community is considered a measure of its social and economic welfare. The paper focuses on the idea of marketing the medical services in the hospitals, and the necessity of the presence of separate directorate for marketing in every hospital to perform the necessary marketing research which is essential for identifying the needs of ill people and their recognized attitudes. It then tries to predict the demand for the medical services and the marketing policies that guarantee provision of the best services and acquisition of new medical devices and equipment, and providing the services that help to satisfy the needs of the ill person.